2021
DOI: 10.23736/s1973-9087.21.06939-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robot-assisted gait training on postural instability in Parkinson's disease: a systematic review

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[31][32][33] Given the heterogeneity of rehabilitation protocols, it is not easy to compare telerehabilitation with other technologically assisted interventions, such as robotic rehabilitation. 17,34 Even if not perfectly comparable, we found that after telerehabilitation programs the BBS achieved similar improvements after robot-assisted gait training and after equal-intensity telerehabilitation protocols dedicated to improving postural stability in PD patients. 25,35 These findings let us argue that a cheaper and home-based approach is feasible in improving postural stability in the same type of population compared with much more expensive robot-assisted gait training.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[31][32][33] Given the heterogeneity of rehabilitation protocols, it is not easy to compare telerehabilitation with other technologically assisted interventions, such as robotic rehabilitation. 17,34 Even if not perfectly comparable, we found that after telerehabilitation programs the BBS achieved similar improvements after robot-assisted gait training and after equal-intensity telerehabilitation protocols dedicated to improving postural stability in PD patients. 25,35 These findings let us argue that a cheaper and home-based approach is feasible in improving postural stability in the same type of population compared with much more expensive robot-assisted gait training.…”
Section: Discussionmentioning
confidence: 77%
“…However, the rehabilitation has many advantages: it can be delivered with low-cost tools25; patients living far away from the rehabilitation center can be reached by a clinician, those without the access to transportation may use it; rehabilitation sessions can be delivered also during the pandemic lockdown and it avoids the interruption of rehabilitation for long-term disabilities, such in the case of PD 31–33. Given the heterogeneity of rehabilitation protocols, it is not easy to compare telerehabilitation with other technologically assisted interventions, such as robotic rehabilitation 17,34. Even if not perfectly comparable, we found that after telerehabilitation programs the BBS achieved similar improvements after robot-assisted gait training and after equal-intensity telerehabilitation protocols dedicated to improving postural stability in PD patients 25,35.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the Consensus has promoted a large exchange of views, fostering all the people involved to share different perspectives and needs. To date, the CICERONE Consensus promoted important evidence on the impact of robotics in stroke (Calabrò, Sorrentino, et al, 2021;Morone, Palomba, et al, 2021), multiple sclerosis (Bowman et al, 2021;, Parkinson's disease (Carmignano et al, 2022;Picelli et al, 2021) and spinal cord injury (Morone, de Sire, et al, 2021). The dissemination of the CICERONE Consensus results is a contribute to national and international perspectives on how to improve functional outcomes of patients living with neurological conditions.…”
Section: Indications From the Cicerone Consensus Conferencementioning
confidence: 99%
“…For the lower limbs, the robot-assisted gait training (RAGT) has been widely implemented to target the regaining and the improvement of patient's mobility, walking ability, and balance. For this purpose, different types of robotic devices (i.e., exoskeletons, end-effectors, soft-robots) have so far been implemented to target diverse chronic and complex diseases (of a traumatic, vascular or neurodegenerative nature) like stroke [5,6], traumatic brain injury (TBI) and spinal cord injury (SCI) [7,8], multiple sclerosis (MS) [9,10], and Parkinson's disease (PD) [11,12], reporting evidence in favor of their feasibility and an improvement in patient autonomy in the activities of daily living (ADLs) and health-related quality of life (HRQoL). Moreover, prior research has also observed, beyond motor improvement, the psychological impact of implementing this technology, reporting for example significant post-intervention changes in patients' depression and anxiety symptoms along with increased well-being [13,14].…”
Section: Introductionmentioning
confidence: 99%